Evaluating Some Physical and Hydrodynamic Properties of Subsurface Soil Layer in Some Locations in the Syrian Coast under Present Conditions of Utilization (Latakia University Journal -Biological Sciences Series, 2013)
In this study which is conducted to evaluate some physical and hydrodynamic properties of subsurface soil layer in some locations scattered in the Syrian coast, it was found that the apparent bulk density in the subsurface of the soils studied did not differ significantly from the limit values ​​that should not be exceeded except for Albahloulih soil (forest soil). The aerobic capacity of soil– the pores are larger than 10 microns- decreased in all the studied soils to about less than half the limit value 10% except for Albahloulih soil (forest) which exceeded the limit value up to 11.37%. The hydraulic conductivity of saturated soils was less than the threshold value allowed in all the locations except for the pine forest which was 0.82 m/day. The study indicates that the change in the average secondary particle diameter after wet sift ranged between 1.43-2.32 mm, therefore the stability of the structural units for the surface soil layer was medium for all the studied soils.The degree of soil compaction in the subsurface soil layer reached 90.91% in Zlin soil (citrus), 90.18% in Trjano soil (vegetables), and 90.13% in Alkabo soil (uncultivated), thus exceeding the permitted limit values​​. It was 83.03% in Albahloulih soil (Forest) which was slightly less than the threshold value. Empirical constants were identified for these soils in the carrier subsurface soil layer which ranged between 0.0036 and 0.000008 for constant (a); while they ranged between 10.3903 and 15.7142 for constant (b) values. Thus, all the studied soils except forest soils need to be reclaimed in their subsurface layers.